INHAUST AND EXHAUST VALVES GAP EFFECTS ON AN ENGINE PERFORMANCES - Puspawan, Angky (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
Valves is the part in an engine determining engine performance. The setting of the valves is to determine the composition of air and fuel in their combustion room. The mixing of the air and the fuel is the key of the engine performance. Dinamometer test was being conducted for the gap variation of the valves of 0.03 mm, 0.05 mm, and 0.07 mm each either for inhaust valve and exhaust one. The optimum of the engine performance of gasoline fuel as measured from the torque, the power, and the specific fuel consumption was at 0.05 mm of both.